Memórias de militares dissidentes (1964-1985): depoimentos à Comissão Nacional da Verdade - Silva, Bruno Almeida (2023)
This research aims to analyze the dissent that a group of military personnel expressed in relation to the institutional guidelines adopted by the Armed Forces after the military coup of 1964 and during the dictatorship that followed until 1985. The roots of the divergences and the political-institutional repercussions that were felt by the group were investigated using as the main source the set of testimonies of dissident military personnel, collected by the National Truth Commission (CNV), installed in 2012. These testimonies, collected in 2013 and 2014, made it possible to prove that they were the target of systematic political persecution and various arbitrary acts, without disregarding that the statements of those involved occurred over a period of more than three decades after the events analyzed. It is understood that the legal-political context in which the repression against these military personnel is developed and justified is supported in theoretical-conceptual terms by the National Security Doctrine (NSD), which provided for the elimination of any and all actions that could be considered subversive and dangerous to the support and maintenance of the military dictatorship. Another fundamental pillar supporting the dictatorship is related to the concept of State Terrorism (ST), which would justify the strictest control of the social order as a result of a state affected by a constant threat of social disarticulation. Dissidences within the military were treated rigorously, since internal disputes were not permitted, since a correlation was assumed between the breakdown of the hierarchical order of the Armed Forces and the possibility of fragmentation of the regime by its intrinsic forces. Realizing that there was a gap in research on dissidence within the military, the problem of this work was the organization of the testimonies and their possibilities of shedding light on this particular issue, since most of the historiography addresses the defection of students, union members and/or urban and rural workers. The actions of dissident military personnel, who questioned the coup in 1964 and rose up against the repression that lasted for 21 years, are important to counter the idea that there was perfect ideological cohesion within the military institution.